The Impact of Digital Health Platforms on Children’s Well-Being - Rizwan Faris Syafiq; Hafiz Hakim (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2022)
Digital health platforms are transforming the way healthcare services are delivered to children, enabling easier access to medical care and monitoring of health conditions. This paper explores the impact of digital health technologies such as health apps, telemedicine, and wearable devices on children's physical and mental well-being. It evaluates the benefits and risks of using these technologies, including improvements in health management and potential concerns regarding screen time and data privacy.